To simplify the expression \( \sqrt[3]{16xy^6} \), we can break it down into its prime factors and simplify accordingly.
First, let's rewrite \( 16 \) and \( y^6 \):
- \( 16 = 2^4 \)
- \( y^6 = (y^2)^3 \)
Now, we can rewrite the expression:
\[ \sqrt[3]{16xy^6} = \sqrt[3]{2^4 \cdot x \cdot (y^2)^3} \]
Applying the property of radicals, we can separate this into two parts:
\[ \sqrt[3]{2^4} \cdot \sqrt[3]{x} \cdot \sqrt[3]{(y^2)^3} \]
We know that \( \sqrt[3]{(y^2)^3} = y^2 \). Now for \( \sqrt[3]{2^4} \), we can simplify it:
\[ 2^4 = 2^3 \cdot 2^1 \implies \sqrt[3]{2^4} = 2 \cdot \sqrt[3]{2} \]
Putting it all together, we have:
\[ \sqrt[3]{16xy^6} = 2 \cdot \sqrt[3]{2} \cdot y^2 \cdot \sqrt[3]{x} = 2y^2 \sqrt[3]{2x} \]
That means the simplified form of the original expression is:
\[ 2y^2 \sqrt[3]{2x} \]
Since none of the given options directly matches with \( 2y^2 \sqrt[3]{2x} \), it's possible that there may have been a typo or misunderstanding in the options provided.
Please double-check the options to ensure there are no mistakes, or let me know if there are any clarifications on the format of the result you’re looking for.